Tankyrase inhibition interferes with junction remodeling, induces leakiness, and disturbs YAP1/TAZ signaling in the endothelium - Ma, Nan; Wibowo, Yohanes Cakrapradipta; Wirtz, Phillip; Baltus, Doris; Wieland, Thomas; Jansen, Sepp R. (Naunyn-Schmiedeberg's archives of pharmacology, 2023)
Tankyrase inhibitors are increasingly considered for therapeutic use in malignancies that are characterized by high intrinsic β-catenin activity. However, how tankyrase inhibition affects the endothelium after systemic application remains poorly understood. In this study, we aimed to investigate how the tankyrase inhibitor XAV939 affects endothelial cell function and the underlying mechanism involved. Endothelial cell function was analyzed using sprouting angiogenesis, endothelial cell migration, junctional dynamics, and permeability using human umbilical vein endothelial cells (HUVEC) and explanted mouse retina. Underlying signaling was studied using western blot, immunofluorescence, and qPCR in HUVEC in addition to luciferase reporter gene assays in human embryonic kidney cells. XAV939 treatment leads to altered junctional dynamics and permeability as well as impaired endothelial migration. Mechanistically, XAV939 increased stability of the angiomotin-like proteins 1 and 2, which impedes the nuclear translocation of YAP1/TAZ and consequently suppresses TEAD-mediated transcription. Intriguingly, XAV939 disrupts adherens junctions by inducing RhoA-Rho dependent kinase (ROCK)-mediated F-actin bundling, whereas disruption of F-actin bundling through the ROCK inhibitor H1152 restores endothelial cell function. Unexpectedly, this was accompanied by an increase in nuclear TAZ and TEAD-mediated transcription, suggesting differential regulation of YAP1 and TAZ by the actin cytoskeleton in endothelial cells. In conclusion, our findings elucidate the complex relationship between the actin cytoskeleton, YAP1/TAZ signaling, and endothelial cell function and how tankyrase inhibition disturbs this well-balanced signaling.
Gesehen am 20.11.2023